URGENCY OF CODING BASIC LEARNING FOR PRE-SCHOOL PARTICIPANT : ROADMAP FOR PREPARING GOLDEN INDONESIA 2045 - Febri Pramudya Wardani; K.P.Suharyono Soemarwoto Hadiningrat (JIPOWER : Journal of Intellectual Power, 2025)
As Indonesia progresses toward its vision of "Indonesia Emas 2045," fostering a digitally literate and innovative generation becomes imperative. Introducing coding education to early childhood learners provides a critical foundation for digital literacy, computational thinking, and problem-solving skills. This paper explores the significance of coding education in early childhood, emphasizing its role in cognitive and social development. Using play-based and developmentally appropriate methods, young learners can engage with coding concepts in meaningful and enjoyable ways. The study also discusses the challenges, such as limited resources and teacher training, and presents strategies for overcoming these barriers, including professional development programs, low-cost coding tools, and public-private partnerships. By embedding coding into early childhood education, Indonesia can prepare a generation capable of driving innovation and technological progress, contributing to the realization of Indonesia Emas 2045.